Asuhan Kebidanan Komprehensif Pada Ny N Umur 22 Tahun Dengan Kekurangan Energi Kronik Di Puskesmas Bumiayu Tahun 2023 - Tyas Andreani; Endang Susilowati; Khunelis Khunelis (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Background: KEK is one of the risk factors for pregnancy causes complications and maternal death. The global maternal mortality rate due to CED is 37%, maternal deaths in Central Java Province in 2020 were 530 cases. The maternal mortality rate in Brebes district is 62 cases. At the Bumiayu Health Center, the maternal mortality rate in 2020 was 2 cases. The aim is to be able to carry out Comprehensive Midwifery Care for Mrs N aged 22 years with Chronic Energy Deficiency at the Bumiayu Community Health Center using Varney's seven-step midwifery management and SOAP Research Method: this research is a qualitative descriptive research with a case study approach. The results: of Comprehensive Midwifery Care for Mrs N were that during pregnancy KEK was found. Delivery was normal and the newborn was found to be underweight. In neonates, boils were found on the legs and the baby's body temperature was high, then appropriate management was carried out so that the problem was resolved. During the postpartum period, the stitched wound was found to be still wet, then ointment was given to solve the problem. Mother uses birth control implant. Conclusion: care has been carried out in accordance with midwifery service standards.